На восток: [роман] / Сергей Протасов - Протасов Сергей Альбертович (Серия "Военная фантастика", 2022)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 57074 / Цена: 403.15 / Сис.шифр: 84(2=411.2)6 / Авт.знак: П 83 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44